2011
DOI: 10.1007/s11426-011-4304-0
|View full text |Cite
|
Sign up to set email alerts
|

Impurity analysis of gentamicin bulk samples by improved liquid chromatography-ion trap mass spectrometry

Abstract: Several gentamicin bulk samples from different origins were investigated using an LC/MS method. LC equipped with ion trap MS with positive ionization was performed on a Capcell Pak C 18 (AQ) column with the mobile phase containing 50 mM trifluoroacetic (TFA) and methanol. Impurities present in batches of gentamicin bulk samples were elucidated and compared according to their fragmentation behavior. In total seventeen impurities present in samples, five impurities were not elucidated and two compounds were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…After 30 days the only major degradants observed were gentamines arising from the cleavage of the A-ring from the B-C gentamicin ring system. All the LC–MS peaks observed in this study could be attributed to previously reported gentamicin impurities [30] , [31] , [32] . Thus, there was no evidence that gentamicin underwent substantive unique degradation pathways when applied as a device coating at readily detectable levels .…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…After 30 days the only major degradants observed were gentamines arising from the cleavage of the A-ring from the B-C gentamicin ring system. All the LC–MS peaks observed in this study could be attributed to previously reported gentamicin impurities [30] , [31] , [32] . Thus, there was no evidence that gentamicin underwent substantive unique degradation pathways when applied as a device coating at readily detectable levels .…”
Section: Resultssupporting
confidence: 69%
“…The extracts obtained from the stability studies were also subjected to LC–MS analysis to screen for common gentamicin impurities and degradants. The characteristic ions for many of these gentamicin impurities have been previously reported [30] , [31] , [32] . Total ion count chromatograms showed the presence of the five gentamicin C components.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…LC equipped with ion trap MS with positive ionization was performed on a Capcell Pak C18 (AQ) column with the mobile phase containing 50 mM trifluoroacetic (TFA) and methanol for the determination of Gentamicin in bulk samples [122] .…”
Section: Chromatographic Methodsmentioning
confidence: 99%